Pengaruh Kesehatan dan Keselamatan Kerja (K3) serta Disiplin Kerja Terhadap Produktivitas Karyawan pada PT. Sahabat Anugerah Sejati - Lisa Oktavia; Efan Elpanso (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
The Indonesian construction industry faces significant challenges with high workplace accident rates affecting employee productivity. PT. Sahabat Anugerah Sejati recorded 15 workplace accidents in 2024 alongside deficits in Personal Protective Equipment (PPE) provision, impacting operational efficiency. This study aims to analyze the effect of Occupational Health and Safety (K3) and Work Discipline on Employee Productivity at PT. Sahabat Anugerah Sejati. The research employed quantitative methodology using explanatory design with cross-sectional approach. The population consisted of 50 construction field employees, with total sampling (census) technique applied. Data collection utilized structured questionnaires with 5-point Likert scale measuring three constructs: K3 (4 indicators), Work Discipline (3 indicators), and Employee Productivity (3 indicators). Analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results demonstrate that K3 significantly influences productivity (coefficient = 0.594, t-statistic = 4.175, p-value = 0.000), Work Discipline significantly affects productivity (coefficient = 0.316, t-statistic = 2.826, p-value = 0.005), and both variables simultaneously explain 70.9% of productivity variance (R² = 0.709, F-statistic = 46.437, p-value = 0.000). The study concludes that integrated occupational health and safety systems combined with consistent work discipline management are essential for enhancing construction worker productivity and organizational performance.